A global mindset – still a prerequisite for successful SME internationalization? - Lasse Torkkeli; Niina Nummela; Sami Saarenketo (Emerald, 2022)
The concept of global mindset was introduced more than a decade ago as a prerequisite for successful internationalisation of small- and medium-sized enterprises (SMEs). However, the pace of global integration and globalisation has accelerated, and complexity has increased. Therefore, the authors ask: To what extent is global mindset still a critical driver for successful international expansion of SMEs? We are particularly interested in learning how global mindset is reflected in the decision making of internationalising SMEs in Finland. To answer this question, we test four propositions which concern the relationship between global mindset, decision-making logic and SME performance. Our empirical study is based on a cross-sectional sample of Finnish SMEs, and the authors find that global mindset seems to be linked to both effectual decisionmaking logic and improved international performance. On the other hand, in our data set effectual decision making and SME performance were not linked; thus, global mindset predicts international rather than overall performance of the Finnish SMEs. Overall, this study confirms the continued relevance of the global mindset concept. Furthermore, it indicates the connection between global mindset and entrepreneurial decision making and that their joint effect is relevant when explaining entrepreneurial internationalisation.
Key success factors of SME internationalisation: A cross-country perspective